(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
Based on an analysis of two sonnets (one by Gongora, the other by Sandoval Zapata), this article addresses the similarities and dissimilarities in the treatment of common topics in the Baroque: the butterfly and the flame. The explanation of the different discursive strategies by the Spanish and the Mexican sonnetists reveals not only the architecture of the baroque metaphor and conceit, but the literary and epistemological implications of the possibility of replacing the substituted term in the metaphorical translation.